(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
Pregnancy is accompanied by profound alteration of thyroid economy and relative iodine deficiency. Sub-optimal thyroid function in pregnancy is associated with impaired neuro intellectual development. Urinary iodine concentration is increased during pregnancy. The aims of this study were to evaluate urinary iodine level in pregnant women and also to elucidate its correlation with thyroid parameters (TSH&FT4) in pregnancy. This was a case control study carried out in the Department of Biochemistry, jointly with the Antenatal and Thyroid Clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the period of July 2003 to June 2004. Urinary iodine excretion was measured in 100 subjects of age range 20-35 years. Among them 60 were pregnant at first trimester and primi gravid. Rest 40 were non-pregnant women who were taken as control. Urinary iodine was measured by Wet digestion based on Sandell-Kolthoff principle. Thyroid Stimulating hormone (TSH) and free thyroxin (FT4) were measured by the AxSYM (Abbott -USA) by applying Micro particle Enzyme Immune Assay (MEIA) principle. The data was reported as Mean± SE; the mean age of the pregnant and nonpregnant women were 25.03±0.48 yrs and 25.20±0.60 yrs respectively. No significant difference was found regarding age. The median urinary iodine of pregnant women was 438.13µg/l (range240.50-490.0) and that non pregnant women was 412.50µg/l (range 240.0-473.75µgl). Mean serum TSH were 1.29±0.15 and 1.97±0.18 mIU/L and mean serum FT4 were 14.51±0.41 and 16.30 ±0.41pmol/L in pregnant and non pregnant women respectively. Urinary iodine level was significantly increased in pregnant women compared to that of the non pregnant group (p<0.05). A significant negative correlation was found between urinary iodine and serum TSH (p<0.01) whereas a positive correlation between urinary iodine and serum FT4 level is p<0.05 in pregnant and p<0.01 in non pregnant group. Urinary iodine excretion is increased in pregnancy than that in non pregnant women. Clinically and biochemically all the subjects were euthyroid and excretion rate of iodine in all subjects were above the normal range. Bangladesh J Med Biochem 2015; 8(1): 21-26